Navigating Challenges and Teaching Through Lived Experiences as Graduate Student Instructors - Cervantes, Marisa V.; Inlow, Alana R. (Teaching and Learning Inquiry, 2022)
Historically, graduate students across academic disciplines have been expected to teach courses in their field, at the college level, without sufficient guidance. This is known as a stressful and difficult experience, but for some graduate students this can be compounded by their positionality, both in the hierarchy in academia as well as their individual minoritized statuses (racial, sexual, gender, or otherwise.) Brought about by our own experiences and struggles, this paper addresses two primary questions: (1) How do our identities impact our experiences as graduate student instructors? And (2) How do we use lived experiences as sociologists and instructors to create a better learning experience for our students? We answer these questions and end the discussion with a call to action, highlighting anti-racism and disrupting the status quo of academia. The call to action is especially pertinent considering the current social and political tensions laid bare by the COVID-19 pandemic and the continuous fight for racial justice and equity.